Implementasi Magiclock Pada Proses Pembelajaran Matematika Kelas 6 MI Kholidiyah - Anandia Anugerah Gusti; Hadi Dwi Siswanto; Amiliya Hanim Nur Faidah; Carina Rizky Aprilia; Ima Chusnul Chotimah (ALFIHRIS : Jurnal Inspirasi Pendidikan, 2023)
The reality in schools shows that in mathematics education, there is still a tendency for teachers to rarely use teaching aids or media. Teachers use simple teaching aids or media, far from capturing students’ attention because they do not pay attention to aspects such as color composition, proportionality, and effective packaging. Such a situation makes mathematics learning uninteresting and enjoyable, resulting in suboptimal support for students in acquiring mathematical concepts. Therefore, there is a need for innovation in mathematics education. By using innovation of Magiclock, a specially desaigned learning medium for the subject of mathematics, particularly for plane geometry and solid geometry topics, this research aims to determine the influence of implementing Magiclock in mathematics education for 6th-grade students at MI Kholidiyah. Qualitative research with a case study method was employed for this study. The 6th-grade students of MI Kholidiyah in the academic 2023/2024, while the object of the study is the implementation of Magiclock in the mathematics learning process. The results of the research obtained during the mathematics learning process for the 6th grade at MI Kholidiyah, using Magiclock, indicate that, based on interviews, the use of this media is highly effective in mathematics education. Students are enthusiastic, do not get bored, and find it easier to understand the topics of plane geometry and solid geometry during the learning process.